Ethics´s Code - Gonzalez Beltrones, Adria Velia (UNIVERSIDAD DE SONORA, 2023)
Ethics’s Code of Biolex Revista Jurídica of the Law Department is based on the values ​​established by the legislation that governs the University of Sonora, where they are distinguished by their preponderance, values ​​such as honesty, respect and tolerance, social responsibility, ethics, responsibility, solidarity, justice, autonomy, equity, commitment to nature, academic freedom and research, which frame the work and the academic and scientific responsibility of Biolex collaborators. It also adheres to the National and International Conventions on Copyright signed by the World Intellectual Property Organization, to which Mexico belongs.